Laboratory methods in enzymology : cell, lipid and carbohydrate - Lorsch, Jon (Methods in enzymology, 2013)
These volumes of Methods in Enzymology contain the protocols that made up the on-line Methods Navigator. Our philosophy when we selected the protocols to include in the Navigator was that they should be for techniques useful in any biomedical laboratory, regardless of the system the lab studies. Each protocol was written by researchers who use the technique routinely, and in many cases by the people who actually developed the procedure in the first place. The protocols are very detailed and contain recipes for the necessary buffers and reagents, as well as flow-charts outlining the steps involved. Many of the chapters have accompanying videos demonstrating key parts of the procedures. The volumes are broken into distinct areas: DNA methods; Cell-based methods; lipid, carbohydrate and miscellaneous methods; RNA methods; protein methods. Our goal is that these protocols will be useful for everyone in the lab, from undergraduates and rotation students to seasoned post-doctoral fellows. We hope that these volumes will become dog-eared and well-worn in your laboratory, either physically or electronically.